Switzerland : Financial Sector Assessment Program; Technical Note; The Swiss Banking System; Structure, Performance, and Medium-Term Challenges. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note discusses the banking system structure, performance, and medium-term challenges for Switzerland. The note discusses that the Swiss banking sector has been undergoing a substantial consolidation over the last 10 years, but retains a rich collection of institutional types operating in various business segments. Consolidation has been partly driven by competitive pressures following the burst of the housing market bubble and entailed a substantial reduction in the number of institutions and branches. Smaller banks have been also developing owing to various types of cost-sharing arrangements.